K.H. AHMAD DAHLAN’S (1869 – 1923) THOUGHT AND HIS STRUGGLE FOR THE ABOLITION OF FEUDALISM THROUGH REFORMATION OF ISLAMIC EDUCATION - Suswandari, -; Suwarno, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
This article examines the founder of the Muhammadiyah, K. H. Ahmad Dahlan (1869–1923) and the reformation of Islamic education he had proclaimed as an attempt to abolish all feudalism force in society towards a realistic and democratic modern society. The clerical reformist, K. H. Ahmad Dahlan played an essential role and was the key for the improvement and the reawakening of Muslim society so as to abandon the rooted feudal cultural practice. This article first discuss the childhood of K. H. Ahmad Dahlan and his education. The article then discusses the socio-cultural context of feudalist Muslim society within his neighborhood. Then, the article also discusses the Islamic education reformation proclaimed by K. H. Ahmad Dahlan referring to his notion on Islamic education reformation, his view on the relation between religion and mind, as well as his political view.